Exposição ocupacional de bombeiros a hidrocarbonetos policíclicos aromáticos medidos pelo uso de pulseiras de silicone - Silva, Priscila Leite (2023)
Worker health is fundamental to public health, especially for those exposed to harmful substances during their work shifts, such as firefighters. This exposure can directly impact the health of these workers, making its investigation important. To identify, through the use of silicone bracelets, the presence of aromatic polycyclic hydrocarbons harmful to the health of firefighters from a Southwest Paraná Military Fire Brigade exposed during their work shifts, as well as to understand the sociodemographic profile of the participants. This is a quantitative, exploratory, descriptive, cross-sectional study with the collection of sociodemographic and workplace data. Data collection occurred in four stages: (1) sociodemographic questionnaire, (2) preparation and application of silicone bracelets, (3) evaluation of substance concentrations in silicone bracelets, (4) chromatographic analysis of substances resulting from workers' exposure in the workplace, and analysis using the Statistical Package for Social Sciences SPSS version 23.0. After the use of the bracelets, chromatography generated the minimum and maximum values of substances found in the samples (bracelets). Naphthalene, Acenaphthene, and Acenaphthylene showed values below the detection levels in chromatography, while Anthracene had an average value of 1.63 ± 3.08 ug/ml, present in all samples used by firefighters on normal duty days, students during training, and instructors. When analyzing the association of substances and the group of exposed firefighters, non-exposed firefighters, and students, in the exposed group, the most present substances were Fluoranthene (93.8%) and Indeno (1,2,3-cd) Pyrene (71.4%), for students, Benzo (g,h,i) Perylene (100%) was present in all samples followed by Pyrene (92.3%). When evaluating cancer risk factors and the presence of substances in passive devices, it is observed that among those with BMI as a cancer development risk factor, 71.4% of samples presented Indeno (1,2,3,c-d) Pyrene. Family history of cancer was significantly associated only with Benzo (a) Pyrene (p<0.05). Individuals with the presence of Fluorene did not engage in physical activities and all the physically active individuals did not present Fluorene 90% (p < 0.05). Of the six bracelets placed on Personal Protective Equipment stored in a firetruck, Anthracene and Benzo (k) Fluoranthene were present on all three days of the study in all six samples. It is concluded that polycyclic aromatic hydrocarbons are carcinogenic substances, and firefighters are in constant contact with them, either in active firefighting or in activities at the fire station, posing an occupational health risk that can result in acute and/or chronic occupational diseases and cancer.